Child-dog faeces assemblages and children's engagements in activist art. Issue 6 (2nd November 2021) - Watson, Debbie; Morgan, Eric; Bull, Katie
ABSTRACT: Dog fouling is recognised as antisocial, unhealthy and illegal in England, yet it persists. Much action against dog fouling happens in communities and impacts are largely unrecorded. Here, we report an activist project with primary-aged children in Bristol, England that resulted in dog fouling reductions near schools and reflects on the role of children in effecting social change in their local environment. The paper takes a New Materialist turn, de-centring experience from the individual child to the child in assemblages of more-than-human relations. Photos of children's interventions against dog fouling are presented to explore how they have used material resources and creativity to emphasise the health and social risks of faeces from a child's perspective. This provides a focus on child–faeces–environment assemblages where children adopt methods of activist art that comprise matter including the faeces to convey a new relational ontology of dog fouling and a reifying of the 'problem'.